PENERAPAN PERMAINAN BAKIAK DALAM MENGEMBANGKAN KECERDASAN MAJEMUK PADA ANAK 5-6 TAHUN DI KB/TK AULAADUL YAMIN - Karmila, Karmila; R, Marmawi; Yuniarni, Desni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This research aims to determine the application of the traditional game of Bakiak in developing compound intelligence in children aged 5 6 years in KB/TK Aulaadul Yamin Pontianak. This research method was descriptive with a qualitiative approach and was a type od action research. The research sample was all students in group B in KB/TK Aulaadul Yamin Pontianak, as many as 16 children. The research instrument used was an observation sheet as the data colletion tool using observation and documentaion techniques. The results showed that a childs compound intelligence could develop after being given action. The given action wa the activity of playing the tradisional game of Bakiak. The result showed that compound intelligence, especialy kinesthetic intelligence through traditional games of Bakiak, made in cycle I was 12,5%, then developed in cycle II to 81,25% and interpersonal intelligence from cycle I by 25%, then developed in cycle II to 87,5%. Thus, childrens compound intelligence, particularly kinesthetic and interpersonal intelligence, can be developed through play activities with traditional Bakiak games